Case reportDermatomyositis with sudden onset – case report - Grodzka, Danuta (Reumatologia/Rheumatology, 2007)
A case of acute dermatomyositis (DM) masked with bilateral shoulder joint pain syndrome and urticaria medicamentosa is described. In rheumatological practice, cases of sudden onset of dermatomyositis and myositis occur rarely. The suspicion of acute DM occurred in a patient already in ER (admission room) of Szpital Wojewódzki in Bydgoszcz and thanks to the immediate visual diagnostics and immuno-laboratory tests the patient was diagnosed early. Treatment with the pulses of methylprednisolone caused regression of symptoms, clear general health improvement and normalization of the results of laboratory tests.